A randomized comparison of the i‐gel™ with the self‐pressurized air‐Q™ intubating laryngeal airway in children. Issue 4 (6th January 2015) - Kim, Min‐Soo; Lee, Jae Hoon; Han, Sang Won; Im, Young Jae; Kang, Hyo Jong; Lee, Jeong‐Rim; Cravero, Joseph
Summary Background Supraglottic airway devices with noninflatable cuff have advantages in omitting the cuff pressure monitoring and reducing potential pharyngolaryngeal complications. Typical devices without cuff inflation available in children are the i‐gel™ and the self‐pressurized air‐Q™ intubating laryngeal airway (air‐Q SP). To date, there is no comparative study between these devices in pediatric patients. Aim The purpose of this randomized study was to compare the i‐gel™ and the self‐pressurized air‐Q™ intubating laryngeal airway (air‐Q SP) in children undergoing general anesthesia. Methods Eighty children, 1–108 months of age, 7–30 kg of weight, and scheduled for elective surgery in which supraglottic airway devices would be suitable for airway management, were randomly assigned to either the i‐gel or the air‐Q SP. Oropharyngeal leak pressure and fiberoptic view were assessed three times as follows: after insertion and fixation of the device, 10 min after initial assessment, and after completion of surgery. We also assessed insertion parameters and complications. Results Insertion of the i‐gel was regarded as significantly easier compared to the air‐Q SP (P = 0.04). Compared to the air‐Q SP group, the i‐gel group had significantly higher oropharyngeal leak pressures at all measurement points and significantly lower frequencies of gastric insufflation at 10 min after initial assessment and completion of surgery. The air‐Q SP group had better fiberoptic views than the i‐gel group at all measurement points. Conclusion Our results showed that the i‐gel had easier insertion and better sealing function, and the air‐Q SP provided improved fiberoptic views in children requiring general anesthesia.